Temporal variation of bird assemblages in a wetland: influence of spatial heterogeneity - Ronchi Virgolini, Ana Laura (2013)
The temporal variation of bird assemblages at three sites within a wetland of the Parana River was examined. The aim was to obtain an overview of the influence of spatial heterogeneity on communities in such a variable environment as the wetlands. We recorded 1,662 individuals belonging to 139 species from 40 families. There were no significant differences between sites in richness, abundance nor diversity. Species richness in the first year was greater than during the second year. Number of resident and migrant species decreased in the second year. Community composition differed between the two years of study and was significantly different among seasons. Species were grouped into 19 trophic guilds. In this study, number of species and their abundances were not significantly different among sites; there were differences in the composition of birds among sites. Thus, the structure of the environments influenced the composition of assemblages in different areas. Guild composition remained fairly constant between years and among seasons. Geomorphological and hydrological dynamics of the river produce a heterogeneous availability of habitats and resources that affect the composition of bird assemblages. Annual and seasonal changes in meteorological variables can lead to changes in the structure and/or composition of those assemblages.